Zakat expenditure and economic growth in the Federal Territory of Malaysia - Yusoff, Mohammed; Densumite, Sorfina (2012)
This research paper aims to examine the impact of zakat distribution on growth in the Federal Territory Malaysia. Specifically, an econometric study is carried out to examine the ability of zakat expenditure to affect real economic growth in the Federal Territory Malaysia by employing various econometric procedures such as the unit root tests, the cointegration tests, the vector error-correction model (VECM), and the Granger causality tests. The findings of the study suggest that zakat expenditure has a positive relationship with real GDP in the long-run. The Granger causality test indicates that zakat spending causes real economic growth with no feedback. In other words, zakat expenditure could boost GDP in the Federal Territory Malaysia both in the short-run and long-run.